Changes in antibiotic resistance patterns of Escherichia coli during domestic wastewater treatment - Lefkowitz, Jamie R (Water environment research : a research publication of the Water Environment Federation, 2009)
Changes in antibiotic resistance of Escherichia coli in the different stages of conventional domestic wastewater treatment were investigated. Over two years, more than 3500 E. coli isolates from four stages of the wastewater treatment process were tested for resistance to six different antibiotics. The percent resistance of bacteria from any of the stages was highly variable in different samples. Because of this variability, no statistically significant difference was found in the overall percent resistance of E. coli from influent to effluent. When comparing different stages within samples, however, there seemed to be an increase in resistance to ampicillin and amoxicillin between the raw influent and primary effluent. In addition, the percent of isolates with multiple antibiotic resistance, resistant to more than one and less than five antibiotics, and highly multiple antibiotic resistance, resistant to at least five antibiotics, increased through the treatment process